Longitudinal Course of Physical Function in People With Symptomatic Knee Osteoarthritis: Data From the Multicenter Osteoarthritis Study and the Osteoarthritis Initiative. Issue 3 (March 2016) - Øiestad, Britt Elin; White, Daniel K.; Booton, Ross; Niu, Jingbo; Zhang, Yuqing; Torner, Jim; Lewis, Cora E.; Nevitt, Michael; L valley, Michael; Felson, David T.
Abstract : Objective: Pain and functional decline are hallmarks of knee osteoarthritis (OA). Nevertheless, longitudinal studies unexpectedly reveal stable or improved physical function. The aim of this study was to impute missing and pre–total knee replacement (TKR) values to describe physical function over time among people with symptomatic knee OA. Methods: We included participants from the Multicenter Osteoarthritis Study (MOST) and the Osteoarthritis Initiative (OAI) with incident symptomatic knee OA, observed during the first 30 months in MOST and 36 months in OAI. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) physical function (WOMAC‐PF), the 5‐times sit‐to‐stand test, and the 20‐meter‐walk test were assessed at 4 and 5 years in MOST and at 6 years in OAI. We used a multiple imputation method for missing visits, and estimated pre‐TKR values close to the time of TKR, using a fitted local regression smoothing curve. In mixed‐effect models, we investigated the physical function change over time, using data before and after imputation and calculation of pre‐TKR values. Results: In MOST, 225 (8%) had incident knee OA, with corresponding 577 (12.7%) in OAI. After adjusting for pre‐TKR values and imputing missing values, we found that WOMAC‐PF values remained stable or slightly declined over time, and the 20‐meter‐walk test results changed from stable in nonimputed analyses to worsening using imputed data. Conclusion: Data from MOST and OAI showed stable to worsening physical function over time in people with incident symptomatic knee OA after imputing missing values and adjusting pre‐TKR values.